Optimalisasi Competitive Advantage Pendidikan Islam Melalui Pemanfaatan Teknologi Digital: Studi Kasus di Madrasah Aliyah Miftahul Ulum - Abdurrahman, Abdurrahman; Habibi, Riki; Qirom, Dian Arfani; Iqbal, Muhammad; Gafur, Abdul; Mujahidin, Nakibul (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
This study aims to analyse the competitive advantages of Islamic education through the use of digital technology at Madrasah Aliyah Miftahul Ulum, Roto Village, Krucil District, Probolinggo Regency. This study focuses on how madrasahs apply technology in every learning and administrative activity, such as the use of online learning platforms, learning videos, and digital management systems to improve efficiency and increase the competitiveness of education. This study uses a descriptive qualitative approach with a field study method, through observation, in-depth interviews, and documentation. The informants consisted of the madrasah principal, three teachers, and ten students. The results of the study show that: first, the integration of digital technology at Madrasah Aliyah Miftahul Ulum is realised through an innovative learning atmosphere. Second, it increases students' interest in learning in every lesson. Third, it strengthens the image of the madrasah as a modern and competitive educational institution while maintaining its excellence in competing with other institutions